The Role of Women in Political and Social Life in Ottoman Algeria 1830-1519 AD.: Women in Power are Role Models - رزاق، مسعودة (جامعة وهران2 محمد بن أحمد, 2024)
تسعى هذه الورقة البحثية إلى الوقوف على دور المرأة في الحياة السياسية بمدينة الجزائر العثمانية 1519-1830 م؛ نساء السلطة الحاكمة أنموذجا، ولا يتأتى ذلك إلا بالعودة إلى الكتابات المصدرية التي تؤرخ لهذه الفترة زماناً ومجالاً، والتي تعد قليلة نوعاً ما على اعتبار أن أغلبها أغفل الحديث عن واقع نساء السلطة الحاكمة لحرمتهن أنذاك، وبغض النظر عن ذلك، فقد تمكنا من رصد بعض المعلومات المتناثرة بين الوثائق الأرشيفية والمصادر الأوروبية أو العربية المختلفة، من خلال الاطلاع على ثناياها وتمحيص محتواها للاستفادة منها فيما يخدم الموضوع مجال البحث. This researcher paper seeks to examine the role of woman in political life in ottoman Alger ire (1519-1830 A.D). The woman of the ruling authority is an example, and this can only be achieved by returning to the source writings that date this period in time and field, which are somewhat little considering that most of them neglected to talk about the reality of the woman of the ruling authority due to their sanctity at the time. Regardless of that, we were able to set some information, scattered among archival documents and various European or Arab sources, by reviewing their contents and scrutinizing their content to benefit from them while the topic serves the field of research.
Keywords: تمكين المرأة -- حقوق المرأة -- المشاركة السياسية -- العصر العثماني